New species and records of frog-biting midges from southern Brazil (Diptera: Corethrellidae) - Amaral, André P.; Pinho, Luiz Carlos (Zootaxa, 2015)
Corethrella borkenti sp. n. is described, based on female and male adults, pupae and larvae, collected from tank bromeliads in the Atlantic Forest of southern Brazil. The larva and pupa of C. alticola Lane, 1939 are described for the first time. New distributional records for C. alticola and C. vittata Lane, 1939 extend their distributions to the southern Atlantic Forest. A key to pupae of peruviana group is given.